Real-world outcomes with tisagenlecleucel in aggressive B-cell lymphoma: subgroup analyses from the CIBMTR registry - Frederick L Locke; Grant Schofield; Marcelo Pasquini; Matthew J Frigault; Cameron J Turtle; Stephen Lim; Brian Hill; Samantha Jaglowski; Caron A Jacobson; Gunjan Shah; Daniel J Landsburg; Michael Heim; et al. (Journal for ImmunoTherapy of Cancer)
Background Tisagenlecleucel, a CD19 chimeric antigen receptor T-cell therapy, is approved for adults with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) or high-grade B-cell lymphoma (HGBCL) after ≥2 lines of therapy. When used in real-world settings, tisagenlecleucel has shown similar efficacy and improved safety compared with previous clinical trials. However, long-term data on real-world outcomes are lacking.Methods Clinical data from a cohort of patients treated with tisagenlecleucel in a real-world setting were captured in the Center for International Blood and Marrow Transplant Research registry. The main clinical outcomes analysed included response rate, duration of response, survival, adverse events and clinicopathologic and treatment characteristics that may affect those outcomes.Results As of May 2022, 1159 patients with R/R DLBCL/HGBCL received tisagenlecleucel. The overall response rate was 59.5%, and the complete response rate was 44.5%. With a median follow-up of 23.2 months in the efficacy set (n=968), the 24 month rates of progression-free survival, ongoing response and overall survival were 28.4%, 52.6% and 43.6%, respectively. Grade ≥3 cytokine release syndrome and neurotoxicity were reported in 6% and 7.4% of patients, respectively. Patients with DLBCL (vs HGBCL), complete response before infusion, prior autologous or allogeneic haematopoietic stem cell transplant and lactate dehydrogenase (LDH) within normal limits experienced more favourable efficacy outcomes, and those with Eastern Cooperative Oncology Group performance status of ≥2, ≥3 prior lines of therapy, elevated LDH and fludarabine-based lymphodepleting chemotherapy experienced less favourable safety outcomes.Conclusions This real-world study of tisagenlecleucel for patients with R/R DLBCL/HGBCL shows consistent efficacy and better safety outcomes than the pivotal trial. This study also identifies baseline disease characteristics and prior or concurrent treatments that may affect clinical outcomes.Tisagenlecleucel, a CD19 chimeric antigen receptor T-cell therapy, is approved for adults with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) or high-grade B-cell lymphoma (HGBCL) after ≥2 lines of therapy. When used in real-world settings, tisagenlecleucel has shown similar efficacy and improved safety compared with previous clinical trials. However, long-term data on real-world outcomes are lacking.Clinical data from a cohort of patients treated with tisagenlecleucel in a real-world setting were captured in the Center for International Blood and Marrow Transplant Research registry. The main clinical outcomes analysed included response rate, duration of response, survival, adverse events, and clinicopathologic and treatment characteristics that may affect those outcomes.As of May 2022, 1159 patients with R/R DLBCL/HGBCL received tisagenlecleucel. The overall response rate was 59.5%, and the complete response rate was 44.5%. With a median follow-up of 23.2 months in the efficacy set (n=968), the 24 month rates of progression-free survival, ongoing response, and overall survival were 28.4%, 52.6%, and 43.6%, respectively. Grade ≥3 cytokine release syndrome and neurotoxicity were reported in 6% and 7.4% of patients, respectively. Patients with DLBCL (vs HGBCL), complete response before infusion, prior autologous or allogeneic haematopoietic stem cell transplant, and lactate dehydrogenase (LDH) within normal limits experienced more favourable efficacy outcomes, and those with Eastern Cooperative Oncology Group performance status ≥2, ≥3 prior lines of therapy, elevated LDH, and fludarabine-based lymphodepleting chemotherapy experienced less favourable safety outcomes.In conclusion, this real-world study of tisagenlecleucel for patients with R/R DLBCL/HGBCL shows consistent efficacy and better safety outcomes than the pivotal trial. This study also identifies baseline disease characteristics and prior or concurrent treatments that may affect clinical outcomes.